2018
DOI: 10.1111/asj.12986
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic and anti‐inflammatory effects of aorta and heart tissues of cattle and pigs in the atherosclerosis rat model

Abstract: The aim of this study was to investigate the effects of aorta and heart tissues obtained from cattle and pigs on atherosclerosis disorders. Atherosclerosis model rats were provided with the respective diets consisting of aorta and heart tissues. Administration of each tissue suppressed body weight gain as compared to that of the control. In particular, the aorta tissues of pigs and cattle demonstrated significant suppressions in body weight gain in the model rats. The aorta tissues of pigs and cattle showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
3
9
0
Order By: Relevance
“…Hyperlipidemia is characterized by an increase in triglyceride (TG), total cholesterol (TC), and low-density lipoprotein-cholesterol (LDL-c) and/or a decrease in high-density lipoprotein-cholesterol (HDL-C) [ 5 ]. Increasing evidence has shown that this abnormality in lipid metabolism causes lipid accumulation, oxidative stress, and inflammation, leading to cardiac damage [ 6 , 7 ]. Several researchers have investigated various drugs for the treatment of hyperlipidemia, such as statins; however, as these drugs are related to the development of cell resistance and are associated with adverse effects, new methods for treating hyperlipidemia are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperlipidemia is characterized by an increase in triglyceride (TG), total cholesterol (TC), and low-density lipoprotein-cholesterol (LDL-c) and/or a decrease in high-density lipoprotein-cholesterol (HDL-C) [ 5 ]. Increasing evidence has shown that this abnormality in lipid metabolism causes lipid accumulation, oxidative stress, and inflammation, leading to cardiac damage [ 6 , 7 ]. Several researchers have investigated various drugs for the treatment of hyperlipidemia, such as statins; however, as these drugs are related to the development of cell resistance and are associated with adverse effects, new methods for treating hyperlipidemia are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the high plasma level of the atherogenic index is related to small LDL-cholesterol particles. This is a predictor of conditions such as obesity, insulin resistance and inflammation, and consequently coronary artery disease, diabetes mellitus, and metabolic syndrome [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…All rats were kept under 12-h light-dark cycles at (23±1)°C and (50±5)% humidity, and had free access to food and water. An atherosclerotic rat model was established through endothelial injury of the iliac arteries and feeding with a 2.5% cholesterol diet with 1% glucose (Sigma-Aldrich, Merck KGaA) for 6 weeks as described previously (19). The rats were randomly divided into two experimental groups: i) The control group that received PBS treatment orally and ii) the experimental group that orally received Pts (≥99%, purity; 10 mg/kg/day; Great Forest Biomedical, Ltd.) treatment with a regular diet for 4 weeks.…”
Section: Methodsmentioning
confidence: 99%